(untitled) (Research, Society and Development, 2021)
The chronic kidney disease (CKD), characterized by progressive decrease in renal function, has high importance and prevalence, but many patients are diagnosed late, when renal replacement therapy (RRT) is mandatory, making screening of the disease valuable for clinical evaluation. This study aims to analyze the number of patients diagnosed with CKD of undetermined etiology, as well as the time elapsed between the date of diagnosis of CKD and the onset of RRT, emphasizing the importance of CKD screening in patients with risk factors, known or not. Therefore, an observational, descriptive and retrospective study of 177 medical records of the Milli Clínica Nephrological in Aparecida de Goiânia - GO, was carried out, and the study population was the patients admitted to dialysis from 2018 to 2021. The characteristics evaluated were origin, age group, gender, risk factors for CKD, family history of CKD, time of conservative treatment of CKD, date of diagnosis of CKD, etiology of CKD and date of admission to RRT. Most patients are from Aparecida de Goiânia (n=116), male (n=105), aged between 50-59 years (n= 49), with hypertension (n=118) and/or diabetes (n=69) and without previous conservative treatment (n=112). Thus, it was concluded that CKD is currently an underdiagnosed disease, and its early diagnosis is important to delay the progression of the disease and the patient’s admission to RRT.